Carbon fiber rods in the treatment of cervical spine tumors: a case series and description of a novel surgical technique - Mazzoli, Simone; Tan, Jonathan Jiong Hao; Scotto, Gennaro Maria; Hallinan, James Thomas Patrick Decourcy; Wang, Shilin; Zoccali, Carmine; Luzzati, Alessandro (Frontiers in Oncology, 2025)
IntroductionConventional implant materials used in spinal tumor surgery, such as stainless steel and titanium, may interfere with the planning and delivery of radiotherapy, and pose difficulties for tumor imaging surveillance, due to the influence of implant-induced artefacts. These limitations have led to the development of novel materials such as carbon fiber composites. However, carbon fiber rods are not used in cervical spinal tumor surgery due to the absence of suitable rod calibers for cervical instrumentation. This study aims to propose a technique to utilize carbon rods in cervical spinal tumor surgery.MethodsThis is a retrospective case series of patients who underwent cervical spinal tumor surgery between November 2020 and September 2022. A customized titanium connector was used to allow connection of a carbon rod to the cervical/occipital instrumentation.ResultsThere were 11 patients included. Mean age was 59.5(range 21-80) years. In 2/11(18%) cases, en-bloc resection was performed; in 5/11(45%), intralesional debulking; in 4/11(36%), separation surgery. Mean construct length was 9(range 7-11) levels; mean number of non-instrumented levels was 3(range 2-5). 9/11(82%) patients did not require anterior reconstruction. Postoperative radiotherapy/hadron therapy was successfully administered to five patients - 3/11(27%) patients underwent postoperative radiotherapy; 1/11(9%), pre-/postoperative radiotherapy; 1/11(9%), postoperative hadron therapy. At two years of follow-up, there were no cases of loss of spinal alignment, implant pull-out, or breakage. Imaging surveillance was able to detect local tumor recurrence in one patient.ConclusionsThe results of our study demonstrate that this is a valid method of utilizing carbon rods in cervical spinal tumor surgery, with their accompanying biomechanical advantages.